O trabalho dos músicos em Belo Horizonte: da satisfação à permanência na ocupação e desigualdades - Jonas da Silva Henrique (2022)
The musician’s professional trajectory is characterized by several peculiarities that makes it distinct from the occupations found in the conventional labor market. Among these distinctions, it is observed that people who spend their time in the world of musical work receive two types of income: pecuniary and non-pecuniary. Menger (1999) argues that non-pecuniary income is related to the satisfaction of the exercise of his office, associated with the perception of success, self-realization, the possibility of creating, autonomy at work, among other returns. Although in the activity of musician are the characteristics of non-pecuniary returns, which increase satisfaction with work, Menger (2006) describes what this environment is composed of characteristics typical of the oversupply of labor, such as; very low middle income, distorted income distribution and also little impact on the level of education on income. In addition, there is high informality, underemployment conditions and individuals who occupy two or more jobs. In view of these aspects, Alper and Wassall (2006) point out that the intemperes found in the field of artistic work, influence the abrupt and involuntary interruption in the professional trajectory, accelerating the process of transition to non-artistic jobs or even to inactivity. Based on the stylized facts described, this research has as general objective to examine the factors associated with participation and continuity in the work activity of musicians, as well as the factors associated with satisfaction (or not) at work and distribution of income. Thus, specifically, the objective is to evaluate whether the musician derives satisfaction with his work; to observe the vicissitudes that abbreviate the musician's professional trajectory; explore the relationship between educational level and income derived from music, and; measure the magnitude of intragroup income inequalities in the field of work of musicians. For this, it is based on a collection of primary data carried out between February and December 2020, capturing information about job satisfaction, professional trajectory, income and personal characteristics. To measure the universe and make the sample calculation of the field research, the group of musicians working in Belo Horizonte who are registered in the Order of Musicians of Brazil - OMB was taken as reference. The choice of the city of Belo Horizonte as the central location of this study occurs because several Brazilian musicians, groups and musical movements, with national and international recognition, began their careers in this city, such as clube da Esquina in the 1960s and 1970s, national pop rock, heavy metal and its ramifications in the 1980s, 90 and 2000, instrumental music, fusion and jazz from the 2000s, in addition to the production of classical music and the Minas Gerais Philharmonic Orchestra (created in 2005) and the traditional Symphonic Orchestra (created in 1977). The results found in this study highlight that the level of satisfaction of musicians working in Belo Horizonte is positively driven by the following characteristics: contributor to social security as a musician, music as main occupation and higher education specialized in music. These characteristics were also important for musicians to remain in occupation throughout 2020, mainly due to the atypical moment caused by the COVID-19 pandemic. In relation to income differentials, it is hypothesized that the musicians' incomes do not correlate linearly with the different levels of schooling. It was observed that the musicians who started their professional trajectories still very young and satisfied in the occupation are more likely to obtain higher incomes. Regarding intragroup inequalities, it was found that age group and educational level are the characteristics that are most associated with the concentration of income in the musicians’ field of work.